2016
DOI: 10.1097/hnp.0000000000000162
|View full text |Cite
|
Sign up to set email alerts
|

Men in Nursing: Intention, Intentionality, Caring, and Healing

Abstract: The purpose of this article is to amplify the results section of a grounded theory study on how men in nursing view and experience intention, intentionality, caring, and healing. This is the second grounded theory study addressing intentionality in healing. The first study included a female population. The theory that was generated-Intentionality: The Matrix of Healing (IMH)-is examined with these new data. The results are compared with issues generally faced by men in nursing and how they described their beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
1
15
0
Order By: Relevance
“…While 12 male nurses in a qualitative study reported perceiving touch as a means of expressing care and compassion, they felt unprepared and unsupported in their use of expressive touch. 38 Similar results were found in Evan’s 35 qualitative study aimed at exploring male nurses’ experiences regarding the use of touch, in which male nurses reported fear of accusation, a heightened sense of vulnerability, and impediment of their ability to complete the caring work they came into the profession to do. In a review of literature completed in 2013, the lack of education about touch was blamed for male nurse’s tendency to seek out low-touch/high-tech or administrative positions within the nursing profession and was labeled as a failure to protect male nurses from potential false accusations.…”
Section: Resultssupporting
confidence: 60%
“…While 12 male nurses in a qualitative study reported perceiving touch as a means of expressing care and compassion, they felt unprepared and unsupported in their use of expressive touch. 38 Similar results were found in Evan’s 35 qualitative study aimed at exploring male nurses’ experiences regarding the use of touch, in which male nurses reported fear of accusation, a heightened sense of vulnerability, and impediment of their ability to complete the caring work they came into the profession to do. In a review of literature completed in 2013, the lack of education about touch was blamed for male nurse’s tendency to seek out low-touch/high-tech or administrative positions within the nursing profession and was labeled as a failure to protect male nurses from potential false accusations.…”
Section: Resultssupporting
confidence: 60%
“…Studies about nursing and men report practice challenges, such as, gender stereotypes and stigma (Cheng et al, 2018;Chiarella & Adrian, 2014;Cottingham et al, 2016;Harding, 2007Harding, , 2008Weaver et al, 2014), ambiguous professional identity (Cottingham, 2018;Wallen et al, 2014), and caring and empathy (O'Lynn & Krautscheid, 2011;Penprase et al, 2015;Sundus & Younas, 2020;Zahourek, 2016). What is evident from the literature is the challenging and problematic nature of male nurse touch, specifically the perception of sexualized touch in the provision of body care (Blackley et al, 2019;Cottingham et al, 2016;Evans, 2002;Fisher, 2009;Harding et al, 2008;MacWilliams et al, 2013;O'Lynn & Krautscheid, 2011, 2014Whiteside & Butcher, 2015;Zahourek, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies reported on the influence of gender on career progression and nursing leadership (Achora, 2016; Asif, 2019; Aspinall et al, 2021; Gauci et al, 2022; Mao et al, 2021; Rajacich et al, 2013; Saleh et al, 2020; van der Heever & van der Merwe, 2021; Zahourek, 2016; Zeb et al, 2020; Zhang & Tu, 2020). Men in women‐dominated professions were believed to experience a ‘glass escalator’ to career success.…”
Section: Resultsmentioning
confidence: 99%